2016
DOI: 10.1186/s12885-016-2879-8
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin inhibits metastatic colorectal cancer growth and interferes with Wnt/β-catenin signaling in CD133+ human colorectal cancer cells

Abstract: BackgroundThe polyether antibiotic Salinomycin (Sal) is regarded as an inhibitor of cancer stem cells. Its effectiveness on human colorectal cancer (CRC) cells in vitro has been demonstrated before. The aim of this study was to establish a murine model to investigate the effectiveness of Sal in vivo. Furthermore, we investigated the impact of Sal on Wnt/β-catenin signaling in human CD133+ CRC cells.MethodsThe two murine CRC cell lines MC38 and CT26 were used to analyze the impact of Sal on tumor cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…Of note is that SAL acted synergistically with 5FU towards drug-resistant A2780 OvCa cell line. A similar effect was presented in studies concerning colorectal and hepatocellular carcinoma, which indicated the neutral or synergistic effect of the combination of SAL and 5FU [48,49]. In case of GEM, which is mostly used as a secondary line of chemotherapy after the development of resistant disease in OvCa, we did not observe the synergistic effect of combined SAL and GEM in both OvCa cell lines, as was found over their action in pancreatic carcinoma cell lines [50,51].…”
Section: Discussionsupporting
confidence: 87%
“…Of note is that SAL acted synergistically with 5FU towards drug-resistant A2780 OvCa cell line. A similar effect was presented in studies concerning colorectal and hepatocellular carcinoma, which indicated the neutral or synergistic effect of the combination of SAL and 5FU [48,49]. In case of GEM, which is mostly used as a secondary line of chemotherapy after the development of resistant disease in OvCa, we did not observe the synergistic effect of combined SAL and GEM in both OvCa cell lines, as was found over their action in pancreatic carcinoma cell lines [50,51].…”
Section: Discussionsupporting
confidence: 87%
“…Salinomycin may target chemoresistant tumor cells, inhibiting Wnt/β-catenin and Sonic Hedgehog signaling pathways (Managò et al, 2015). Furthermore, it suppresses the migration of colorectal, breast, lung and colon cancer cell lines as well the invasion of nasopharyngeal carcinoma and bladder cancer cells in vitro (Kopp et al, 2014;Wu et al, 2014;Qu et al, 2015;Klose et al, 2016). Consistently, in vivo studies proved that salinomycin may reduce metastasis formation in mammary tumor mouse model, bladder tumor rat model and intravenous mouse tumor model (Gupta et al, 2009;Kopp et al, 2014;Qu et al, 2015).…”
Section: Therapeutic Targeting Metastasismentioning
confidence: 70%
“…The lower compartment of the chamber was filled with culture medium containing 20% fetal calf serum. Cells were cultured in the absence or presence of Sal for 48 h. Afterward, the medium was changed and the cells were incubated for another 48 h. Membranes were stained with crystal violet solution, and the migrated cells on the lower side of the membrane were isolated from the membrane and quantified by measurement of the absorbance at 540 nm according to the manufacturer’s instructions and as described in [ 11 ].…”
Section: Methodsmentioning
confidence: 99%